PS-C20-7: CARDIOVASCULAR SAFETY OF OLMESARTAN FOR MODERATE HYPERTENSIVE PATIENTS: A MULTICENTER COHORT STUDY USING A COMMON DATA MODEL. (January 2023) - Kim, Ju Hyeon; Lim, Subin; Chung, Se Hwa; Yum, Yunjin; Joo, Hyung Joon; Kim, Yong Hyun; Kim, Eung Ju
Abstract : Objective: Olmesartan has been linked to numerical imbalances of cardiovascular mortality compared to placebo group. There is a paucity of contemporary data on real world evidence of this agent in different study populations. We sought to investigate clinical outcomes between olmesartan and other anti-hypertensive medications in moderately hypertensive patients. Design and method: This multicenter, retrospective study used the Korea University Medical Center database built on electronic health records from 2017 to 2020. Patients prescribed with at least two antihypertensive drugs as combined therapy were followed up for 3 years. The primary endpoint was a composite of all cause mortality, myocardial infarction, stroke, and heart failure. Adjusted outcome was compared with the use of propensity score matching (PSM). Results: Among 20, 835 patients, 3, 508 (16.8%) were olmesartan initiators from Jan 2017 to Dec 2017. Average age was 64 years, 45% were men, and 41% had diabetes. Olmesartan group were younger, more often women, and less likely to have diabetes mellitus and chronic kidney disease. The 3 year cumulative incidence of the composite primary endpoint was similar in both groups (4.9% vs. 5.7%, log rank p = 0.06). After PSM, the adjusted 3 year rate of the primary endpoint was similar between two groups (7.4% vs. 7.1%, log rank p = 0.72). In multivariable analysis, olmesartan use was associated with an adjusted hazard for the primary outcome of 0.95 (95% confidence interval, 0.83 to 1.10). Conclusions: Olmesartan combination for moderately hypertensive patients showed similar cardiovascular outcomes in real world practice, and there is no robust signal for harm with olmesartan use.